2000
DOI: 10.1038/sj.cdd.4400630
|View full text |Cite
|
Sign up to set email alerts
|

Fas-independent apoptosis in T-cell tumours induced by the CD2-myc transgene

Abstract: Depending on the cellular context, the Myc oncoprotein is capable of promoting cell proliferation or death by apoptosis. These observations suggest that apoptosis in response to deregulated gene expression may represent a natural brake to tumour development. The pathways by which Myc induces apoptosis are as yet poorly characterised although recent observations on rat fibroblasts over-expressing Myc have demonstrated a requirement for the Fas pathway. To investigate the role of Fas in Myc-induced lymphomagenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In addition, tumor cell lines derived from mice expressing inducible Myc showed similar rates of inducible apoptosis regardless of their lpr genotype. These results are consistent with the conclusion that activation of cMyc and loss of Fas do not collaborate in T lymphoma development, and that c-Myc-induced apoptosis in Tcells occurs by Fas-independent pathways (Cameron et al, 2000).…”
Section: Consequences Of Deregulated C-myc Expression On Dierentiatiosupporting
confidence: 81%
“…In addition, tumor cell lines derived from mice expressing inducible Myc showed similar rates of inducible apoptosis regardless of their lpr genotype. These results are consistent with the conclusion that activation of cMyc and loss of Fas do not collaborate in T lymphoma development, and that c-Myc-induced apoptosis in Tcells occurs by Fas-independent pathways (Cameron et al, 2000).…”
Section: Consequences Of Deregulated C-myc Expression On Dierentiatiosupporting
confidence: 81%
“…Furthermore, loss of Fas functions in lpr mice was shown to accelerate Myc-induced lymphomagenesis in L-myc transgenic mice (Zornig et al, 1995). However, this finding has been challenged by other in vivo studies showing that loss of Fas or FasL does little to Mycinduced apoptosis or transformation (Cameron et al, 2000), and direct links to other regulators and modifiers of the death receptor pathways have been slow in coming.…”
Section: Dancing With Death Receptorsmentioning
confidence: 68%
“…This might indicate that overexpression of FLIP L favors differentiation of T-cell lymphoma cells or increases the survival of mature CD4 + T-cell lymphoma cells, but does not change the overall tumor burden. Previous studies of Myc-induced CD4 + /CD8 + T–cell lymphoma in the CD2-MYC model in a lpr genetic background showed that deletion of Fas did not accelerate T-cell lymphoma development, although an increased population of CD4 + T-cells was found [50]. Smith et al [45] reported that MYC-expressing CD4 + T cells in the VavP-Myc model was more prone to apoptosis than the corresponding CD4 + /CD8 + T-cells, suggesting that FLIP L might contribute to increased survival of this population in our model system, although this did not contribute to increased T-cell lymphoma over AML ratio.…”
Section: Discussionmentioning
confidence: 85%